2016
DOI: 10.1016/j.cnp.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical skin conductance for quantitative assessment of sweat function: Normative values in children

Abstract: HighlightsSudomotor function can be assessed through the measurement of electrochemical skin conductance using the Sudoscan system.This test is easily done in children and normative data are provided.It can be helpful in case of small fibre neuropathy in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…[ 23 ] In a previous study, ESC measurements in healthy children were found to be similar to those observed in healthy adults. [ 24 ] Good reproducibility has been reported between two sequential measurements performed at rest, and there is no significant variation in ESC after exercise. [ 13 25 ] These advantages make ESC an attractive option for large-scale screening and intervention trials.…”
Section: Discussionmentioning
confidence: 99%
“…[ 23 ] In a previous study, ESC measurements in healthy children were found to be similar to those observed in healthy adults. [ 24 ] Good reproducibility has been reported between two sequential measurements performed at rest, and there is no significant variation in ESC after exercise. [ 13 25 ] These advantages make ESC an attractive option for large-scale screening and intervention trials.…”
Section: Discussionmentioning
confidence: 99%
“…The small sex parameter (~ 0-3) is considered as non relevant for clinical applications and our last model integrating the daily and annual variations also tends to make this effect mostly null. The age parameter was estimated to -0.12 in clinical study, and here around -0.2 3,14,15,17 Although we probably did not filter out all the non-healthy users and we have no information about ethnicity, which is another important confounder of ESC normal values 14,15,17,18 , we can consider that the effect of age should be between -0.1 and -0.2 per year. Thus, the ESC value is reduced by 1 to 2 points per decade for each individual, which should not be neglected in the clinical monitoring of patients at advanced ages to determine the possible evolution of a peripheral neuropathy.…”
Section: Discussionmentioning
confidence: 99%
“…The Quantitative Sudomotor Axon Reflex Test (QSART) is a sensitive and reproducible test of sudomotor function, but is limited by cost and extensive patient preparation time [ 15 , 16 ]. Since electrochemical skin conductance (ESC) depends on sweat gland function [ 17 ], its values may quantify sudomotor function and provide a surrogate marker for autonomic neuropathy. Sudoscan has been developed as a method to measure ESC, with preliminary findings suggesting its potential use as a measure of small nerve fibre function across disorders, such as diabetic peripheral neuropathy [ 16 ].…”
Section: Introductionmentioning
confidence: 99%